Strengthening Social Inclusion and Empowerment for People with Disabilities through the Malang Inclusion Forum - Slamet Daroini; Jumriyah Jumriyah; Inayatur Rosyidah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Persons with disabilities constitutionally have the same rights and status before the law and government. But unfortunately, legal issues, the implementation of Law No. 8/2016 is considered not optimal. The Malang Inclusion Forum as a miniature inclusive society will continue to act as a motor for the disability social movement and control government policies. This research includes qualitative descriptive research and case study research. Data were collected through observation, interviews, documentation and literature study. Determination of sources of information (informants) in this study is purposive sampling with the snowball method. The data that has been obtained were analyzed using the interactive analysis technique of Milles and Huberman. The results of this research are the strengthening of social inclusion for people with disabilities through the Malang Inclusion Forum in the form of disability awareness, disabled people are aware of advocacy, and disabled people are aware of regulations. Meanwhile, empowerment for people with disabilities is in the form of awareness raising and capacity training as well as network development and development.